Knowledge and barriers towards cervical cancer screening among young women in Malaysia - Al-Naggar, R.A.; Low, W.Y.; Isa, Z.M. (Asian Pacific Organization Cancer Prevention, 2010)
Objectives: This study examined the level of knowledge and barriers towards cervical cancer screening of female university students. Methodology: A cross-sectional design was used for 287 female students at a tertiary institution located in Selangor, Malaysia. A name list of all students in the all faculties were obtained from each faculty's registrar and the ethics committee of the Faculty of Health and Life Sciences, approved the study. Respondents completed a consent form before they were given the questionnaire consisting of four sections: socio-demographic characteristics (six questions); risk factor of cervical cancer (six); knowledge about cervical cancer and the Pap smear test (ten); and finally barriers to Pap screening (eleven). Data were analyzed using SPSS version 13. Results: The prevalence of ever having had a Pap test was 6%. Majority of the participants had adequate knowledge about risk factors of cervical cancer. The highest knowledge about cervical cancer risk factor reported by the respondents was having more than one sex partner (77.5%), whereas the lowest was the relationship between HPV and cervical cancer (51.2%). Age, marital status, ethnicity, monthly family income and faculty were significantly associated with knowledge of cervical cancer screening (p=0.003; p=0.001; p=0.002; p=0.002; p=0.001 & p=0.002; respectively). The most common barriers of cervical cancer screening were the Pap smear test will make them worry (95.8%) whereas the least common barrier reported among participants was no encouragement from the partner (8.8%). Conclusion: Some misconceptions and barriers in uptaking Pap smear test are still serious problems among young women. Although knowledge about cervical cancer screening is adequate they have a very poor practice of Pap smear test. The introduction of reproductive health subjects is warranted for all university students.